2.2k views
5 votes
Suppose that the functions g and h are defined for all real numbers x as follows. g(x) = 2x+2, h(x) = 5x. Write the expressions for (g-h)(x) and (g x h)(x) and evaluate (g+h)(-1).

User BenA
by
4.7k points

1 Answer

4 votes

Answer:
(g-h)(x) =-3x+2


(g* h)(x)=10x^2+10x


(g+h)(-1)=-5 .

Explanation:

Given,
g(x) = 2x+2\\ h(x)=5x

To write: the expressions for
(g-h)(x) and
(g x h)(x) .

To evaluate :
(g+h)(-1).

As
(g-h)(x) = g(x)-h(x)


= (2x+2-(5x)) [substituting the values of
g(x) and
h(x)]


= 2x-5x+2=-3x+2

So,
(g-h)(x) =-3x+2

Now,
(g * h)(x)= g(x)* h(x) =(2x+2)* 5x


=2x* 5x +2*5x\\=10x^2+10x\\\\\Rightarrow\ (g* h)(x)=10x^2+10x

Now,
(g+h)(-1)= g(-1)+h(-1) = (2(-1)+2)+(5(-1))=-2+2-5=-5

So,
(g+h)(-1)=-5 .

User Loyalar
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.